Mutants of Actinomyces viscosus T14V lacking type 1, type 2, or both types of fimbriae. - Cisar, J O (1988)
Mutants of Actinomyces viscosus T14V lacking type 1 or type 2 fimbriae or both were selected by their failure to react with rabbit antibodies against either or both fimbrial antigens. Immunospecific double labeling with iron dextran and ferritin-conjugated antibodies showed two types of fimbriae on individual cells of the parent organism, a single type on mutant strains with type 1+2- and type 1-2+ fimbriae and no labeled or unlabeled fimbriae on a type 1-2- fimbria-deficient strain. The mutational loss of one fimbrial antigen did not appear to affect expression of the other, since bacteria with one or two types of fimbriae bound similar amounts of a monoclonal antibody directed against the fimbrial antigen present on both bacterial phenotypes. The strong adsorption of strains with type 1+2+ or 1+2- fimbriae to saliva-treated hydroxyapatite and weak adsorption of those with type 1-2+ or no fimbriae was consistent with the known involvement of type 1 fimbriae in this attachment process. Similarly, the A. viscosus lectin was clearly associated with the expression of type 2 fimbriae, since only the strains with type 1+2+ or 1-2+ fimbriae participated in lactose-sensitive coaggregations with Streptococcus sanguis 34. Further studies using the fimbria-deficient mutant strains showed that aggregation of A. viscosus T14V in the presence of sialidase-treated human saliva involved both types of fimbriae, whereas neither type was required for the lactose-resistant coaggregation of the organism with certain streptococcal strains.